Callose-mediated resistance to pathogenic intruders in plant defense-related papillae - Voigt, Christian A. (Frontiers in Plant Science, 2014)
Plants are exposed to a wide range of potential pathogens, which derive from diverse phyla. Therefore, plants have developed successful defense mechanisms during co-evolution with different pathogens. Besides many specialized defense mechanisms, the plant cell wall represents a first line of defense. It is actively reinforced through the deposition of cell wall appositions, so-called papillae, at sites of interaction with intruding microbial pathogens. The papilla is a complex structure that is formed between the plasma membrane and the inside of the plant cell wall. Even though the specific biochemical composition of papillae can vary between different plant species, some classes of compounds are commonly found which include phenolics, reactive oxygen species, cell wall proteins, and cell wall polymers. Among these polymers, the (1,3)-β-glucan callose is one of the most abundant and ubiquitous components. Whereas the function of most compounds could be directly linked with cell wall reinforcement or an anti-microbial effect, the role of callose has remained unclear. An evaluation of recent studies revealed that the timing of the different papilla-forming transport processes is a key factor for successful plant defense.